2020
DOI: 10.1186/s13568-020-01103-6
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the strategy of metagenomics for exploring the intestinal microecology of sable (Martes zibellina), the national first-level protected animal

Abstract: Sable (Martes zibellina), a member of family Mustelidae, order Carnivora, is primarily distributed in the cold northern zone of Eurasia. The purpose of this study was to explore the intestinal flora of the sable by metagenomic library-based techniques. Libraries were sequenced on an Illumina HiSeq 4000 instrument. The effective sequencing data of each sample was above 6000 M, and the ratio of clean reads to raw reads was over 98%. The total ORF length was approximately 603,031, equivalent to 347.36 Mbp. We inv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 72 publications
(78 reference statements)
0
1
0
1
Order By: Relevance
“…The comparison of sympatric species allows us to study the relative influence of genetic and environmental factors on the composition in the gut microbial community of the species (Moeller et al, 2012 ). Previous researches have shown that the dominant phyla exclusively by species living in sympatry spanned the four major phyla of gut bacteria (i.e., Bacteroidetes, Firmicutes, Proteobacteria, and Actinobacteria) (Huttenhower et al, 2012 ; Yan et al, 2020 ; Ye et al, 2016 ). Proteobacteria and Firmicutes are the most widespread phyla of gut microbiota, and they are commonly observed within gut environments of many mammals, such as human, mouse, and the ruminant animal (Lavrinienko et al, 2018 ; Maurice et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of sympatric species allows us to study the relative influence of genetic and environmental factors on the composition in the gut microbial community of the species (Moeller et al, 2012 ). Previous researches have shown that the dominant phyla exclusively by species living in sympatry spanned the four major phyla of gut bacteria (i.e., Bacteroidetes, Firmicutes, Proteobacteria, and Actinobacteria) (Huttenhower et al, 2012 ; Yan et al, 2020 ; Ye et al, 2016 ). Proteobacteria and Firmicutes are the most widespread phyla of gut microbiota, and they are commonly observed within gut environments of many mammals, such as human, mouse, and the ruminant animal (Lavrinienko et al, 2018 ; Maurice et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…К подроду Martes на территории Евразии относят также лесную (M. martes L., 1754), каменную (M. foina foina Erxleben, 1777) куниц и харзу (M. flavigula Bjddaert, 1785) (1,5,6). За пределами Евразии обитают еще два представителя подрода Martes (7).…”
unclassified